A Comparative Study of the Five Large Universities' Websites in Iran - Shamsosadat Zahedi (Journal of Information Technology Management)
One of the most adaptable and fast-paced media in today’s world is Internet. We can access to what we are looking for by proper connections in Internet. Universities are among those organizations that by designing websites use Internet for interacting with their clients including faculty members, students and other interested people. Websites are a collection of files, graphics, media, contents, database and other information that can be viewed at a designated Uniform Resource Locator (URL) via a web browser. University websites have an ability to combine text with graphic signs and other multimedia for the purpose of exchanging information between universities and the users. This article reveals the findings of a research about the websites of five large universities in Iran: Tehran, Allameh Tabataba’i, Shahid Beheshti, Sharif, and Tarbiat Modares universities. After presenting the findings of this comparative research, the article will end with suggestions aiming at improvement of the websites of Iranian universities.